KELAYAKAN MASKER TEPUNG KENTANG UNTUK PERAWATAN KULIT WAJAH JERAWAT - Hilda Sri Putri; Prima Minerva (Universitas Negeri Padang, 2022)
This research is motivated by they problem of facial skin with acne which causes a lack of self-confidence because it will cause black spots, acne scars on the face. Therefore, researchers chose a potato mask because it can help reduce black spots on acne scars. They purpose of this studyng was to dethermine the feasibility of potato starching masks from the point of view of laboratory tests, organoleptic tests, and hedonic tests. The type of research is an experimental study of potato starch masks. The data collection methods are documentation and questionnaires arranged on a Likert scale consisting of 7 panelists consisting of 2 practitioners, 2 lecturers, and 3 students. The collected data wehre procesing used a percentage descriptive analysist formula. The result of laboratory test research were Vitamin C contained in potato starch masks, namely 70.38 mg / 100gr, vitamin B1 contained in potato starch masks 0.40 mg / 100gr and potatoes containing enzymes catecholase which was characterized by the formation of foam in the sample, and the results The potato starch mask questionnaire obtained a very smooth texture, had a strong aroma, had good stickiness, and was liked by the panelists.